CONTRASTING THEORIES OF PROFIT. - Littleton, A. C. (The Accounting Review, 1936)
Abstract In barter for re-trade, expected profit is a judgment regarding relative subsequent exchangeability of the new thing possessed in comparison with other, as yet, un-possessed desirable things. The test of this pre-judgment comes when the anticipated re-exchange is accomplished. If, subsequent to the first barter-exchange, no third person finds a prospective utility in the goods held for re-exchange, there is no second exchange and no accomplished profit for the trader; also if after a second barter exchange, the goods then newly received should prove not to have the expected utility, there can be no accomplished profit. Valuation is a part of the process of exercising sound judgment in consuming or trading, and forms the basis for all production and merchandising operations. And the ability to make sound judgments regarding consumptive wants and uses, and of trade opportunities exists quite independently of records as such. Reality of profit should not he read into a situation too soon or upon inadequate evidence. This is the basis of the so-called realization principle. When an objective test has verified a personal hope, conviction of reality may safely follow but not before. Anticipated profits are mere opinions and therefore subject to individual bias and mistaken judgment. Realized profits on the other hand have met an objective test, under conditions by which the utility of the goods has been further attested by the independent judgment of a subsequent receiver in exchange. But even such realization may prove to be an incomplete test of reality because today's gains may be consumed by tomorrow's losses if the goods last received prove useless.